Convergence between the Penn Alcohol Craving Scale and diagnostic interview for the assessment of alcohol craving. (December 2019) - Hartwell, Emily E.; Bujarski, Spencer; Green, ReJoyce; Ray, Lara A.
Abstract: Introduction: The Penn Alcohol Craving Scale (PACS) is one of the most widely used instruments to measure craving for alcohol. Recent research has suggested that scores on the PACS can be used as a "stand in" for the diagnostic criterion of alcohol craving with a proposed cutoff of >20 on the PACS indicating a "positive" alcohol craving symptom. The present study examined the convergence between the PACS and face-to-face diagnostic interview for the assessment of alcohol craving. Method: A sample of non-treatment seeking heavy drinkers (N = 338) enrolled in experimental studies of AUD completed the PACS as well as a face-to-face diagnostic interview for AUD, which included the craving item from the Semi-Structured Assessment for the Genetics of Alcoholism (SSAGA). Results: Using the PACS cut-off score of >20, 12.9% (N = 43) of the sample met criteria for alcohol craving compared to 21% (N = 74) of the sample meeting criteria based on the diagnostic interview. Using the PACS cutoff of >20, sensitivity (i.e., true positive rate) was 41% and specificity (i.e., true negative rate) was 95%. Exploratory analyses suggested that a cut-off score of ≥15 achieved the optimal balance of sensitivity (67%) and specificity (81%) in our sample. Conclusions: Advancing the assessment of alcohol craving and the conversion from DSM-IV to DSM-5 diagnostic criteria represents an important research direction. The present study recommends that a PACS score cut off of ≥15 should be used as an indicator of clinically significant alcohol craving in community samples of non-treatment seekers. Highlights: The relationship between self-report and clinician-administered measures of alcohol craving is poorly understood. Previous studies have used the PACS as a stand-in for diagnostic data, using a score of 20 as a cut off. Using a PACS of >20, 12.9% of the sample would meet for craving; however, this cut off yielded poor sensitivity. Exploratory analysis showed a cut off of >15 produced an acceptable balance of sensitivity and specificity in this sample.